2023
DOI: 10.1007/jhep09(2023)091
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entanglement as nonlocal magnetism

Umut Gürsoy,
Juan F. Pedraza,
Guim Planella Planas

Abstract: The Ryu-Takayanagi prescription can be cast in terms of a set of microscopic threads that help visualize holographic entanglement in terms of distillation of EPR pairs. While this framework has been exploited for regions with a high degree of symmetry, we take the first steps towards understanding general entangling regions, focusing on AdS4. Inspired by simple constructions achieved for the case of disks and the half-plane, we reformulate bit threads in terms of a magnetic-like field generated by a current fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Due to the fact that dψ is future-directed and timelike, these Σ(c) are slices. 10 Moreover, as ψ| A = −1/2 and ψ| B = 1/2, they all must also be homologous to A, since all the level sets must have σ A = ∂A as boundary.…”
Section: With S the Proper Distance Along Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that dψ is future-directed and timelike, these Σ(c) are slices. 10 Moreover, as ψ| A = −1/2 and ψ| B = 1/2, they all must also be homologous to A, since all the level sets must have σ A = ∂A as boundary.…”
Section: With S the Proper Distance Along Pmentioning
confidence: 99%
“…This approach has been a fruitful avenue of research in past years. Bit threads have been used to study multipartite entanglement [1][2][3][4][5], holographic monogamy of mutual information [6,7], the hypergraph entropy cone [8], metric reconstruction [9], describe the entanglement structure of a state in terms of a modified Biot-Savart law [10], etc. Furthermore, recent developments extending the thread formulation to Lorentzian manifolds [11] showed that quantities other than entanglement can be formulated in this language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bit threads have been also generalized to its quantum corrected version [45,46] and the covariant version [47]. For other recent progresses on bit threads, please refer to [48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%